Family Communication Crisis in Disaster Management in Serdang Bedagai Regency - Abdurrahman Zuhdi; Abrar Adhani; Rudianto Rudianto (Lembaga Riset Ilmiah, 2026)
Coastal communities are highly vulnerable to hydrometeorological disasters, such as tidal flooding, coastal erosion, and storm surges. Despite the implementation of various disaster risk reduction programs, community preparedness, particularly at the household level, remains relatively low. Previous studies have mainly focused on institutional communication and early warning systems, while studies examining the role of family communication as a micro-level foundation for disaster preparedness remain limited. This study aims to identify the forms of family communication crises in disaster management, analyze the role of family communication in shaping disaster awareness and preparedness, and formulate family communication strategies to enhance community resilience in Bagan Kuala Village, Serdang Bedagai Regency. This study employed a qualitative case study approach using purposive sampling techniques. Data were collected through in-depth interviews, participatory observations, and documentation and were analyzed using data triangulation. The findings indicate that family communication regarding disaster preparedness remains reactive, incidental, and unstructured. Most families only discuss disasters after hazards occur, resulting in limited disaster knowledge, inadequate household emergency planning, and weak preparedness behavior. The study further reveals that regular family communication can enhance disaster awareness, risk perception, and shared responsibility in responding to disaster threats. Based on these findings, four key strategies are proposed: encouraging routine family discussions on disaster risks, developing household emergency plans, involving all family members in disaster education, and strengthening collaboration among families, schools, and communities. The novelty of this study lies in positioning family communication as a strategic micro-level component in building disaster preparedness and resilience among coastal communities. Theoretically, this study extends disaster communication scholarship, which has predominantly focused on institutional aspects, while practically providing recommendations for the development of family-centered disaster mitigation programs.